THE EFFECT OF SERVICESCAPE, PERSONAL SERVICES AND SERVICES ON PASSANGER SATISFACTION THROUGH PERCEIVE VALUE MEDIATION AT TERMINAL 3 SOEKARNO AIRPORT - HATTA - Gadis, Anggraini; Mulyowahyudi, Alugoro (Dinasti Publisher, 2022)
The purpose of this study was to determine the effect of servicescape, personal service and services variables on customer satisfaction through perceived value mediation at Terminal 3 Soekarno Hatta Airport. This type of research is quantitative with data collection methods passenger questionnaire and literature study. The research population is passengers in internasional airline at Terminal 3 Soekarno-Hatta International Airport. The research sample was 240 people, the sampling technique was using probability simple random sampling technique. A analysis and testing of the hypothesis of this study using SEM with PLS software version 3.0. Hypothesis testing results (1) Servicescape take effect positive and _ significant to perceived value. Hypothesis (2) Servicescape no effect positive and significant against Passanger Satisfaction. Hypothesis(3) Personal Service positive and significant effect to Perceive value. Hypothesis(4) Personal Service positive and significant effect to Passanger satisfaction. Hypothesis(5) Services positive and significant effect to Perceive value. Hypothesis (6) Services have no positive and significant effect on Passanger Satisfaction. Hypothesis (7) Perceive value has a positive and significant effect to passanger satisfaction. Hypothesis (8) Indirect influence of servicescape positive and significant to Passanger satisfaction through Perceive value mediation. Perceive value is a full mediator. Hypothesis (9) Indirect influence of Personal Service Positive and significant to Passanger Satisfaction through Perceive value mediation. Perceive value is a partial mediator between personal service and customer satisfaction. Hypothesis (10 ) Indirect Effect of Services positive and significant impact on Passanger satisfaction through perceived value. This means that Perceive value is a full mediator.